Утиськод-а нимдэ?: повесть но веросъёс / Николай Белоногов - Белоногов Николай Егорович (Удмуртия, 1989)
Экземпляры: ф.1 (20190905) / Инвентарный номер: 19763 / Цена: 0.45 / Сис.шифр: 84(2Рос=Удм)6 / Авт.знак: Б 43 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Удм)6